E-Sanction Policy In Online Learning In Universities Based On Cyber Education Service System - Yana Indawati; Hervina Puspitosari; Yovita Arie Mangesti (CV. Inara, 2021)
The rapid globalization of technology, coupled with the pace of technological development, has become an online learning facility that makes it easier to meet face-to-face virtually in the current learning system. Online learning expects students to gain soft skills in the current digital era, especially supported by various Merdeka Campus programs. The E-Sanction policy is a product that is needed with the shift in education in today's digital era. Improvement of the education system based on cyber- service system services. This research is collaborative research between the lecturers of the Universitas Pembangunan Nasional “Veteran” Jawa Timur and the Universitas 17 Agustus 1945 as a higher education institution where researchers teach who have also responsively eliminated face-to-face teaching and learning on campus since the Covid 19 pandemic to suppress the growth of exposure to the Corona 19 virus that becomes a global problem. From the results of this study, it is possible to obtain an overview of the effectiveness of online learning and obtain an e-sanction policy model that can be applied to students so that lectures can run in an orderly manner. Every university has a code of ethics that applies to students and along with online learning conditions, it is necessary to set a code of ethics policy for students in participating in the online learning process. The need for e-sanction applicateions as a means of providing sanctions for violations of the student code of ethics.